2018
DOI: 10.1001/jamaoncol.2017.2993
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pathologic Nodal Staging Quality With Survival Among Patients With Non–Small Cell Lung Cancer After Resection With Curative Intent

Abstract: The prognostic value of pN stratification depends on the thoroughness of examination. Differences in thoroughness of nodal staging may explain a large proportion of intercontinental survival differences. More thorough nodal examination practice must be disseminated to improve the prognostic value of the TNM staging system. Future updates of the TNM staging system should incorporate more quality restraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 27 publications
4
92
0
Order By: Relevance
“…25 These data and subsequent work suggest that positive nodes may be overlooked in a clinically significant proportion of patients, with resultant consequences on long-term survival. [25][26][27] Troublingly, several studies have also reported that a considerable proportion of patients with early-stage disease are simply not adequately evaluated for nodal disease (so-called Nx patients), likely underrepresenting the true incidence of N1 disease. 17,25,[28][29][30][31] In their analysis of data from the National Cancer Database, Khullar and Data are presented as n (%), as median (interquartile range), or as indicated.…”
Section: Commentmentioning
confidence: 99%
“…25 These data and subsequent work suggest that positive nodes may be overlooked in a clinically significant proportion of patients, with resultant consequences on long-term survival. [25][26][27] Troublingly, several studies have also reported that a considerable proportion of patients with early-stage disease are simply not adequately evaluated for nodal disease (so-called Nx patients), likely underrepresenting the true incidence of N1 disease. 17,25,[28][29][30][31] In their analysis of data from the National Cancer Database, Khullar and Data are presented as n (%), as median (interquartile range), or as indicated.…”
Section: Commentmentioning
confidence: 99%
“…A recent multi-institutional prospective study showed that the introduction and compliance with basic quality measures for lymph node evaluation by surgeons and pathologists (examination of at least one N1 lymph node, at least 10 total lymph nodes, and at least three mediastinal nodal stations) significantly increased lymph node yield, improved survival, and better stratified postoperative stage-specific survival curves. 34,35 The authors also implicated variations in the quality of intraoperative nodal staging for the intercontinental differences in postoperative survival. 35 With the increasing use of sublobar resection for small GGNs, which seem to have a low risk of nodal involvement, the extent of required nodal evaluation is an emerging controversy.…”
Section: Surgery For Early-stage Nsclcmentioning
confidence: 99%
“…34,35 The authors also implicated variations in the quality of intraoperative nodal staging for the intercontinental differences in postoperative survival. 35 With the increasing use of sublobar resection for small GGNs, which seem to have a low risk of nodal involvement, the extent of required nodal evaluation is an emerging controversy. Noticeably, no lymph nodes were examined in 49% and 23% of wedge and segmental resections, respectively, for stage I tumors less than or equal to 2 cm, and the number of nodes examined was revealed as an independent risk factor for survival, whereas the extent of resection was not.…”
Section: Surgery For Early-stage Nsclcmentioning
confidence: 99%
“…[97][98][99] There was additional evidence for the inherent value of surgical lymphadenectomy, indicated by better survival in subsets of patients meeting more stringent definitions of nodal staging quality. 62 The more detailed the requirement for nodal staging quality (such as criteria set by the National Comprehensive Cancer Network [NCCN], Union for International Cancer Control/American Joint Committee on Cancer), the better was survival and the more discriminating was the nodal staging system (separating pN0 v pN1 v pN2). 62,100 Linking the environmental structure of care delivery to outcomes, patients who received care within a structured multidisciplinary care program received more thorough staging, and higher rates of stage-appropriate treatment (including surgery for early-stage disease) than those whose care was provided in "serial care" settings.…”
Section: Intraoperative Lymph Node Evaluationmentioning
confidence: 99%
“…62 The more detailed the requirement for nodal staging quality (such as criteria set by the National Comprehensive Cancer Network [NCCN], Union for International Cancer Control/American Joint Committee on Cancer), the better was survival and the more discriminating was the nodal staging system (separating pN0 v pN1 v pN2). 62,100 Linking the environmental structure of care delivery to outcomes, patients who received care within a structured multidisciplinary care program received more thorough staging, and higher rates of stage-appropriate treatment (including surgery for early-stage disease) than those whose care was provided in "serial care" settings. 101 2017 brought evidence that directly linked specific process measures (attainment of the NCCNrecommended quality of resection [anatomic resection, negative margins, examination of N1 lymph nodes and examination of a minimum of three mediastinal nodal stations] and the ratio of the observed-to-expected rate of incomplete resection) to survival: two readily measured surgical quality benchmarks.…”
Section: Intraoperative Lymph Node Evaluationmentioning
confidence: 99%